EpiDiverse Toolkit: a pipeline suite for the analysis of bisulfite sequencing data in ecological plant epigenetics. (12th November 2021) - Nunn, Adam; Can, Sultan Nilay; Otto, Christian; Fasold, Mario; Díez Rodríguez, Bárbara; Fernández-Pozo, Noé; Rensing, Stefan A; Stadler, Peter F; Langenberger, David
Abstract: The expanding scope and scale of next generation sequencing experiments in ecological plant epigenetics brings new challenges for computational analysis. Existing tools built for model data may not address the needs of users looking to apply these techniques to non-model species, particularly on a population or community level. Here we present a toolkit suitable for plant ecologists working with whole genome bisulfite sequencing; it includes pipelines for mapping, the calling of methylation values and differential methylation between groups, epigenome-wide association studies, and a novel implementation for both variant calling and discriminating between genetic and epigenetic variation.